Lucas Guevara - Díaz Guerra, Alirio, 1862- (Recovering the U.S. Hispanic Literary Heritage Project publication., 2003)
"This is the English translation of Lucas Guevara, the first Spanish-language novel of immigration to the United States, Written by Colombian emigre Alirio Diaz Guerra and originally published in the United States in 1914, the novel establishes the structure and formula that numerous other Spanish-language narratives produced in this country would take up over the course of the twentieth century." "Freshly arrived from the pristine countryside of South America, Lucas quickly becomes a victim of the modern Metropolis, its treacherous rogues, and its immoral women. Lucas finds no streets paved with gold. Instead he ultimately succumbs to the pleasures of the flesh and becomes an unscrupulous predator himself."